(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Нrebenyk T. V. The motivation peculiarities to the studies of the students of higher educational establishment of the I-II level of accreditation. The article contains questions of the students’ motivation to the studies and determines the state of this problem in theory and practice of higher school. The author emphasizes the actuality, meaningfulness and sharpness of the activity direction of pedagogical collectives; analyses the main notions, presents the results of the investigations and distinguishes peculiarities of forming the students’ motivation to the studies.